2005
DOI: 10.1080/10412905.2005.9698978
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Species in the GenusAchillea

Abstract: Based on the present knowledge of essential oil composition of species belonging to the genus Achillea the factors, which may influence the composition with regard to plant biology, production and application are discussed.According to studies from the last 15 years, a mean of 54 compounds have been identified in samples of different species. Among them, the largest number of components (149 compounds) were found in the oils of A. millefolium, A. pannonica and A. collina. The monoterpenes, 1,8-cineole, camphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
58
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 60 publications
3
58
1
Order By: Relevance
“…Plants from this genus are, in wide diversity, spread in Serbian territory, where 19 species have been recognized (Gajić, 1975). Regarding pharmacological properties, the most important species belong to the Millefolium group, which is characterized by wide morphological, cytological and chemical diversity, and it has been botanically systemized in few subspecies whose chromosome numbers are ranging from diploid (2n=18) to octaploid (8n = 72) forms (Nemeth, 2005). Therefore A. millefolium L. sensu lato is the developing evolutionary taxon currently considered as an aggregate of 12 species (Saukel and Langer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Plants from this genus are, in wide diversity, spread in Serbian territory, where 19 species have been recognized (Gajić, 1975). Regarding pharmacological properties, the most important species belong to the Millefolium group, which is characterized by wide morphological, cytological and chemical diversity, and it has been botanically systemized in few subspecies whose chromosome numbers are ranging from diploid (2n=18) to octaploid (8n = 72) forms (Nemeth, 2005). Therefore A. millefolium L. sensu lato is the developing evolutionary taxon currently considered as an aggregate of 12 species (Saukel and Langer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also reported that the essential oil yield and its composition were related to genetic and climatic factors, soil conditions, phase of growth (vegetative or flowering stage), and part of the plant [16]. Thus, the study of the chemical composition of essential oils in relation to environmental factors might provide information on how to determine the chemical polymorphism of this genus in Tunisia.…”
mentioning
confidence: 99%
“…The seasonal fluctuation of this chemical class showed a progressive decrease from winter to summer. The most important epoxide was 13-epimanoyl oxide (16), which reached the maximum content (6.95%) in the oil from Hawaria leaves harvested in January. In contrast, for all four locations, manoyl oxide was detected only in oils from leaves harvested in spring.…”
mentioning
confidence: 99%
“…However, chamazulene was found within the three principal constituents only in a small part of investigated A. millefolium essential oils [10][11][12][13][14]. The first predominant components in the oils were determined as sabinene, β-pinene, β-phellandrene, 1,8-cineole, borneol, ocimene, artemisia ketone, linalool, α-and β-thujone, camphor, borneol, fenchyl acetate, bornyl acetate, fragranol, lavandulyl acetate, ascaridole, caryophyllene, caryophyllene oxide, germacrene D, α-copaene, α-and β-bisabolol, eudesmol and δ-cadinol [4,11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, the composition of essential oils was investigated mainly for the yarrow oils that are produced by all aerial parts of the plant.…”
Section: Introductionmentioning
confidence: 99%